Integrated Quality Management as an Effort to Improve the Quality of the Catering Department at SMK Negeri 3 Malang - Laili, Afifatul; Alfandie, Alya Irrzaq Nahya; Jannah, Asa Maghfirotul; Tio, Aurelia Jovita Putri; Agustin, Desika; Supriyanto, Achmad (Journal of Education for Sustainability and Diversity, 2023)
Quality educational institutions are those that continuously improve the quality of their education. This education should be given from an early age, because at an early age it is necessary to develop creativity in students. The purpose of this study was to examine the analysis of integrated quality management at SMK Negeri 3 Malang with Total Quality Management (TQM). In this study we used a research method with a qualitative approach. The data collection technique used was by giving a questionnaire to the principal of SMK Negeri 3 Malang. The results of this study are researchers analyzing how the integrated quality management process works with TOM, to understand how SMK Negeri 3 Malang seeks to apply the principle of providing customer satisfaction, what are the special programs at SMK Negeri 3 Malang as a form of optimal service, and superior accreditation as a form of principle continuous institutional improvement at SMK Negeri 3 Malang, which illustrates that the implementation of integrated quality management in SMK education institutions in early childhood is very necessary in supporting continuous improvement.